Analisis Kebutuhan dan Perancangan Antarmuka Aplikasi Kolaborasi Penelitian Menggunakan User Experience Design Process - Abdul Karim Batubara; Franindya Purwaningtyas; Raissa Amanda Putri (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
In conducting collaborative research involving more than one researcher, a system is needed that can improve the performance of researchers in various ways. This study captures the challenges faced by researchers in collaborative research and defines the requirements for collaborative research systems needed to address these challenges. From the analysis of the needs obtained, the researchers designed a collaboration application interface. Collaboration applications are needed to facilitate communication between researchers, search for articles, share publications, and other applications. The distribution of questionnaires and interviews were conducted to obtain the requirements needed for the development of a collaboration system. This research informs system developers to support the development of collaborative systems. In this study, the level of need for a research collaboration system in the university environment will be analyzed along with an analysis of its needs and the design of the user interface.